N-octanoyl dopamine is superior to dopamine in protecting graft contractile function when administered to the heart transplant recipients from brain-dead donors - Loganathan, Sivakkanan; Guo, Yuxing; Jiang, Weipeng; Radovits, Tamás; Ruppert, Mihály; Sayour, Alex Ali; Brune, Maik; Brlecic, Paige; Gude, Phillipp; Georgevici, Adrian-Iustin; Yard, Benito A.; Karck, Matthias; et al. (Pharmacological research, 2019)
The major source of heart transplantation comes from brain-dead (BD) donors. However, brain death and myocardial ischemia/reperfusion injury during transplantation may lead to cardiac dysfunction and hemodynamic instability. A previous work demonstrated that pre-treatment of BD donors with dopamine improved the graft survival of heart allograft in recipient after transplantation. However, low-dose dopamine treatment might result in tachycardia and hypertension. Our previous experimental study showed that pre-treatment of BD donor rats with the dopamine derivate N-octanoyl dopamine (NOD), devoid of any hemodynamic effects, improved graft function after transplantation. Herein, we hypothesized that NOD confers superior myocardial protection than dopamine, in terms of graft function. Male Lewis donor rats were either subjected to sham-operation or brain death via a subdurally placed balloon followed by 5.5h monitoring. Then, the hearts were explanted and heterotopically transplanted into Lewis recipient rats. Shortly before the onset of reperfusion, continuous intravenous infusion of either NOD (14.7μg/kg/min, BD+NOD group, n=9), dopamine (10μg/kg/min, BD+Dopamine group, n=8) or physiological saline vehicle (sham, n=9 and BD group, n=9) were administered to the recipient rats. In vivo left-ventricular (LV) graft function was evaluated after 1.5h reperfusion. Additionally, immunohistochemical detection of 4-hydroxy-2-nonenal (HNE, an indicator of oxidative stress) and nitrotyrosine (a nitro-oxidative stress marker), was performed. After heart transplantation, systolic and diastolic functions were significantly decreased in the BD group compared to sham. Treatment with NOD but not dopamine, resulted in better LV graft systolic functional recovery (LV systolic pressure BD+NOD 90±8 vs BD+Dopamine 66±5 vs BD 65±4mmHg; maximum rate of rise of LV pressure dP/dtmax BD+NOD 2686±225 vs BD+Dopamine 2243±70 vs BD 1999±147mmHg/s, at an intraventricular volume of 140μl, p<0.05) and myocardial work compared to BD group. The re-beating time (time to restoration of heartbeat) was significantly shorter in BD+NOD group than that of BD hearts (32±4s vs. 48±6s, p<0.05), Dopamine treatment had no impact on all of these parameters. Furthermore, NOD as well as dopamine decreased HNE and nitrotyrosine immunoreactivity to the same level. NOD is superior to dopamine in terms of protecting LV graft contractile function when administered to the heart transplant recipients from BD donors.
Gesehen am 13.05.2020